Return Signal Momentum - Fotis Papailias; Jiadong Liu; Dimitrios D. Thomakos (Queen's University Belfast, Queen's Management School, 2019)
A new type of momentum based on the signs of past returns is introduced. This momentum is driven primarily by sign dependence, which is positively related to average return and negatively related to return volatility. An empirical application using a universe of commodity and financial futures offers supporting evidence for the existence of such momentum. Investment strategies based on return signal momentum result in higher returns and Sharpe ratios and lower drawdown relative to time series momentum and other benchmark strategies. Overall, return signal momentum can benefit investors as an effective strategy for speculation and hedging
Keywords: G11; G12; G15; 330